Nutritional Status in Parasitized and Nonparasitized Children from Two Districts of Buenos Aires, Argentina - Orden, Alicia Bibiana (2014)
The Program for the Control of Intestinal Parasites and Nutrition was designed to intervene in small communities to prevent and control the effects of parasitic infections on children’s health. Objectives: To analyze the association between nutritional status and parasitic infection in suburban and rural children from Buenos Aires, Argentina. Methods: Nutritional status was assessed by anthropometric (weight, height, BMI, skinfolds, upper arm circumference, muscle, and fat upper arm areas) and biochemical (Hb, Ca, Mg, Zn, and Cu) indicators. Parasitological analysis were made on both serial stool and perianal swab samples. A total of 708 children aged 3–11 were measured. The biochemical analysis included 217 blood samples and the parasitological study included 284 samples. Results: Anthropometric status was similar in both settings with low rates of underweight and stunting (<6%), and high rates of overweight (17%) and obesity (12%). Ca deficiency was significantly higher in suburban children where 80% of them were hypocalcemic. Around 70% of fecal samples contained parasites. Among infected children, the most prevalent species were Blastocystis hominis and Enterobius vermicularis (43%) followed by Giardia lamblia (17%). Differences in parasitological status between districts were not significant. In the suburban district parasitized children were lighter, shorter, and had a lower upper arm circumference than their non-infected peers. No differences in anthropometric status were seen among infected and uninfected rural children. Conclusions: The results suggest an association between intestinal parasites and physical growth in suburban children. Rural children seem to be protected against the effects of parasitic infection.